The Authority Of Notaries In Making Prenuptial Agreement Deeds: A Study Of The Dimensions Of Professional Ethics - Mubarak, Ahmad (Fakultas Syariah UIN Antasari, 2025)
A prenuptial agreement is an important legal instrument to protect property rights in marriage, the making of which requires an authentic deed by a Notary. This authority is regulated in UUJN and Marriage Law, and requires compliance with professional ethics. This study aims to examine the authority of Notary and the application of professional ethics in the making of the deed. Using normative legal research methods, this study highlights the role of Notary as not only a deed maker, but also a guardian of the principles of justice, free will and impartiality. It is found that the practice in the field often faces ethical challenges such as inequality of bargaining position and potential conflict of interest. Therefore, ethical capacity building, strict due diligence, and strong professional supervision are needed to maintain the legal and moral legitimacy of deeds.